Peningkatan Kemampuan Membaca dan Menerjemah Bahasa Arab dengan Menggunakan Metode al-Qawa'id wa al-Tarjamah di Pondok Pesantren Darul Amin Pasaman Barat - Nur Patimah (Intiqad: Jurnal Agama dan Pendidikan Islam, 2021)
The ability to read and translate Arabic is part of an important ability to be owned by learners, because without this ability, learners will have difficulty in revealing the meaning contained in written manuscripts in Arabic. In connection with this urgency, the study aims to describe changes in the ability to read and write Arabic using the method of al-Qawa'id wa al-Tarjamah. This study was conducted using experiments, namely researchers doing treathmen to experimental classes. Research data is collected through pre-test and post-test. The study sample was determined in clusters, based on the technique, the study sample amounted to 64 who were members of the experimental class and control class. The results of the experiment proved that there was a significant increase in the ability of learners to read and translate Arabic scripts, the increase was seen from the increase in the acquisition of test results after the treatment.